Personal Brand as a Game Changer in Building the Recognition of Doctoral Students in the Scientific and Academic Environment - Muszyńska, Weronika (Marka osobista jako game changer w budowaniu rozpoznawalności doktorantów w środowisku naukowym i akademickim, 2024)
Although personal brand has been studied in relation to the activity of doctoral students and recognition is considered the key to the development of a scientific career (Duszczyk, 2022), the literature lacks specific research on the relationship between these concepts. The aim of the article is to answer the question whether doctoral students are aware of the importance of personal brand in building their recognition in the scientific and academic environment, and what actions they take in this regard. To achieve this goal, it was decided to conduct a qualitative study in the form of individual in-depth interviews (IDI) on a group of doctoral students of Doctoral Schools (N = 6). As a result, it was found that doctoral students notice the importance of personal brand, but rather do not consider as a game changer in building their recognition.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 2, s. 23-34
Keywords: personal brand; game changers; recognition; doctoral student; marka osobista; rozpoznawalność; doktoranci